FYC Students’ Emotional Labor in the Feedback Cycle - Kelly Blewett (Journal of the Assembly for Expanded Perspectives on Learning, 2020)
This essay explores the emotions first-year composition students experience when receiving feedback on their writing. Culling data from 32 hours of interviews with students, as well as two different data streams students provided regarding their emotional reactions to feedback, I argue that students undergo what Arlie Hochschild calls transmutation as they process feedback on their writing. Two implications are suggested: first, that future studies should utilize non-alphabetic tools for capturing emotion; second, that teachers wishing to assist student reception of feedback should be attentive to building rapport in the classroom. Finally, the essay calls for additional study of the impact of positionality on rapport-building and, in turn, the feedback cycle.
Keywords: Education; Emotional Labor; Student Feedback; Creative Writing